Seroprevalence of syphilis among HIV-infected individuals in Addis Ababa, Ethiopia: a hospital-based cross-sectional study. Issue 4 (2nd April 2013) - Eticha, Begna Tulu; Sisay, Zufan; Alemayehu, Addisu; Shimelis, Techalew
Abstract : Objective: To determine the prevalence of syphilis and its risk factors among people with HIV at a hospital in Ethiopia. Design: A hospital-based cross-sectional study. Setting: This study was conducted at one of the largest public hospitals in Addis Ababa, Ethiopia. Participants: A consecutive 306 HIV-positive patients were recruited prospectively from January to March 2010. For comparative purposes, 224 HIV-negative consecutive attendees at the voluntary counselling and testing centre in the same period were also included. Participants under 15 years of age and treated for syphilis and with a CD4 T-cell count below 50 cells/mm 3 were excluded. Outcome measures: Blood samples and data on sociodemographic and risk factors for syphilis were collected. Sera were screened for syphilis using rapid plasma reagin (RPR) test, and those positives were retested using Treponema pallidum haemagglutination assay (TPHA) test. Results: The seroprevalence of syphilis among HIV-infected individuals was 9.8% compared with 1.3% among HIV-uninfected individuals, OR 8.01 (95% CI 2.4 to 26.6; p=0.001). A comparable rate of syphilis was found among men (11%) and women (8.9%) with HIV infection. Syphilis prevalence non-significantly increased with age, with the highest rate in 40–49 years of age (16.9%). Except a history of sexually transmitted infections, which was associated with syphilis OR 2.25 (95% CI 1.03 to 4.9; p=0.042), other risk factors did not raise the odds of infection. Conclusions: The high prevalence of syphilis among people with HIV infection highlights the need to target this population to prevent the transmission of both infections. Screening all HIV-infected people for syphilis and managing those infected would have clinical and epidemiological importance.